Teledentistry and the Unified Health System: an important tool for the resumption of Primary Health Care in the context of the COVID-19 pandemic - Carrer, Fernanda Campos de almeida (2020)
This “short communication” describes the possibilities of using Teleodontology to expand and qualify health care in oral health care networks. WHO already recommended to its member countries, including Brazil, even before the pandemic, the use of Telehealth as a strategy to improve the quality of its services, especially in the context of universal health systems, as the Unified Health System In the current context, Teleodontology opens opportunities for oral health to resume the offer of various services, remotely, such as: 1. tracking, active search, monitoring users of priority groups, at risk and with systemic problems, monitoring of suspected cases of COVID-19 and its contacts, via telemonitoration; 2. initial listening, individual and collective educational activities, among others, through teleorientation; 3. discussion of clinical cases to define the opportune moment to perform operative procedures among professionals of different levels of care, matrix support, sharing and soluting doubts between professionals or between professionals and teaching and research institutions, through teleconsulting, among others . In addition to a literature review on Teleodontology in the context of the pandemic, an important contribution of this “short communication” is the conceptualization of the terms used and possibilities they offer to SUS professionals, in addition to specifying the possible protocols for recording these activities, in order to provide service managers with secure data for monitoring and evaluating the work process. In addition, we bring a brief discussion with some promising experiences, carried out in the pre- and trans-pandemic context, which can consolidate themselves as important strategies for the resumption of oral health in the post-pandemic scenario.